Transcultural View of Comedy Packed Stereotypes: A Conceptual View towards Stand-Up Comedy with Racial Issues by Russel Pieters - adiella lubis (PRoMEDIA, 2016)
Comedy is an interesting thing to be studied in the repertoire of intercultural communication. Lightweight comedical language could assist the smoothness of communication between cultures, but what if the stereotypes used as objects in a live comedy show with an audience of cultural backgrounds or even different countries? Cultural differences will also affect the state discourse on stand-up comedy will be the main concern in this study. Russel Pieter classified as an international stand-up comedian with English as a foreword, disposition as the Indian race is also a reference that stereotypes in comedy be interesting, in this study the focus was how he delivered comedy with stereotypes material to the audience. Stereotypes in comedy were able to reach the stage of confidence in the audience who watched the comedy, so the impact of stereotypes in comedy can be positive or negative, depending on the material presented by comedian on the stage. Positive material will produce a good effect, and the negative material will result in adverse effects Keyword: Stand-up Comedy, Stereotype